2016
DOI: 10.1186/s41182-016-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Eco-social and behavioural determinants of diarrhoea in under-five children of Nepal: a framework analysis of the existing literature

Abstract: BackgroundWhile diarrhoea is the second major killer among the under-five children in the world with an estimation of 760,000 deaths annually, it stands as a major killer in Nepal with an annual incidence of 500 per 1000 under-five children with diarrhoea. Diarrhoea is responsible for a wide range of morbidity and mortality among children in Nepal. The objective of this review work is to identify the eco-social and behavioural determinants of diarrhoea among the under-five children of Nepal.MethodsA literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 26 publications
(52 reference statements)
15
47
0
1
Order By: Relevance
“…These factors, i.e. poverty and nutrition, have already been established in the literature as determinants of health both in emergency and nonemergency settings (39)(40)(41). We nd a signi cant positive relationship for household wealth, food security and frequency of sickness.…”
Section: Discussionsupporting
confidence: 55%
“…These factors, i.e. poverty and nutrition, have already been established in the literature as determinants of health both in emergency and nonemergency settings (39)(40)(41). We nd a signi cant positive relationship for household wealth, food security and frequency of sickness.…”
Section: Discussionsupporting
confidence: 55%
“…While the level of education attained is deemed important [30, 32, 33, 36, 38, 5154], a lack in knowledge also exists regarding either availability of services, severity of illnesses and/or vulnerability to diseases [48–50, 5658, 6062]. Healthcare practices in households have deep roots in cultural beliefs and gender roles [19] thus a strong education system is required to advance this area. Nepal clearly has work to do to strengthen community level health literacy and this will underpin the attainment of SDG3: Ensure healthy lives and promote well - being for all at all ages .…”
Section: Discussionmentioning
confidence: 99%
“…Gaps to address the social determinants of health exist in Nepal. While Nepal still faces a burden of infectious diseases struggling with inadequate basic hygiene and sanitation along with deep rooted cultural beliefs, the burden of non-communicable diseases is also on the rise [18, 19]. Limited research has been found mentioning health literacy in Nepal [2022] and level of health literacy of the people of Nepal is not known.…”
Section: Introductionmentioning
confidence: 99%
“…According to the framework on eco-social and behavioural determinants of children diarrhea proposed by Budhathoki and colleagues, as well as other influencing factors identified by other studies through a literature review [16,21,35], we considered a range of factors, data of which can be either obtained from NDHS or other open-access databases, as potential risk factors in this study. These factors included children's personal factors (i.e., child's age, child's gender and whether the child living with mother), maternal-related factors (i.e., mother's years of education, mother's age at birth of the child and number of children under five years old in the family), socio-economic factor (i.e., wealth index, type of place of residence, residing status), and household-related factors (i.e., water source, sanitation facility and fuel type), information of which obtained from the NDHS Women's questionnaire.…”
Section: The Datamentioning
confidence: 99%
“…In addition, personal behaviors (e.g., personal hygiene habits) also play an essential role in childhood diarrhea [18]. Budhathoki and colleagues did a framework analysis of eco-social and behavioural determinants of children diarrhea in Nepal, eliciting age, gender, hand-washing behaviour, nutritional status of children, education of mothers, water and sanitation, healthcare services, cultural and societal values and income of the household as the identified determinants [21]. Furthermore, seasonality, environment and climatic factors (e.g., temperature, elevation, humidity and flooding) showed important relationships with diarrhea risk in some studies [22][23][24].…”
Section: Introductionmentioning
confidence: 99%